2021
DOI: 10.3390/ijerph182312714
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Caregivers’ Parenting Styles on the Emotional and Behavioral Problems of Left-Behind Children: The Parallel Mediating Role of Self-Control

Abstract: Childhood is an important period of individual psychological development, and parents’ company and parenting styles are highly significant to children’s personality cultivation and mental health. With the advancement of China’s modernization and urbanization, left-behind children without their parents’ company have become a growing concern. Compared with children raised by their parents, left-behind children are more likely to show social maladaptation and mental health problems. This study explored the mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 68 publications
3
4
1
Order By: Relevance
“…In this study, our findings indicate that parenting style was substantially correlated with EBPs among Chinese adolescents, which was in line with other studies [ 59 , 60 ]. According to our results, parental emotional warmth was negatively associated with the EBPs and subscales.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, our findings indicate that parenting style was substantially correlated with EBPs among Chinese adolescents, which was in line with other studies [ 59 , 60 ]. According to our results, parental emotional warmth was negatively associated with the EBPs and subscales.…”
Section: Discussionsupporting
confidence: 93%
“…However, the relations between parenting style and child's behavioral problems have been mixed. In contrast, previous studies have shown non-directional (13) or bidirectional (14) relations between parenting style and behavioral problems in TD children. One of the theoretical mechanisms underlying the association between parenting style and behavior problems in children is the coercion theory (15).…”
Section: Introductioncontrasting
confidence: 77%
“…The imposition of high levels of parental control and intervention may suppress children’s intrinsic motivation, subsequently limiting their exploration and adaptation abilities ( Guan et al, 2018 ). Additionally, research suggests that individuals with higher levels of self-control demonstrate better regulation of mood and emotions, whereas poor self-control is associated with anxiety and depression ( Özdemir et al, 2014 ; Yen et al, 2014 ; Pan et al, 2021 ). Given that poor self-control serves as a risk factor for mood disorders, it may contribute to comorbidity between anxiety-depression, substance use, and Internet addiction during later childhood ( Na et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%